ANALISIS YURIDIS PELAKSANAAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PADA PT. PASIFIK AGRO SENTOSA - Eric Vincent; Sri Bakti Yunari (Jurnal Hukum Adigama, 2020)
Social and environmental responsibility activities are important in building the company's image and reputation, which in turn increases the trust of both consumers and business partners of the company. PT. Pasifik Agro Sentosa (PAS) itself is an agribusiness company engaged in oil palm plantations, sugar cane plantations, sugar mills and refined sugar industry. Specific regulations governing the implementation of social responsibility must be in line with the provisions carried out by PT. PAS is in accordance with article 3 paragraph 1 of Government Regulation Number 47 of 2012. Methodology uses empirical legal research (juridical empirical). Empirical law research is oriented towards primary data (research results in the field). Research specifications in the form of descriptive analytical research implementation of social and environmental responsibility of PT. Pacific Agro Sentosa. The results of the analysis of the authors that the implementation of social and environmental responsibility of PT. PAS by following the applicable laws and regulations of course also helps the government in terms of community empowerment, by building schools, polyclinics, and other institutions that are needed. Obstacles encountered were differences in understanding with the community and social jealousy from the community / village. In conclusion, the implementation of TJSL conducted by PT. PAS in accordance with article 3 paragraph 1 of Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies based on community empowerment. Suggestions from the author that there is a need to reduce TJSL in the form of charity.